Oral administration of Melissa officinalis or Bahuinia forficata infusions reduce the postischemic recovery of hearts from hypothyroid rats - Ragone, María Inés (2019)
Drinking infusions of Melissa officinalis (Moff, “lemon balm”) or Bahuinia forficata (Baf, “cow´s hoof”) are clinically contraindicated in hypothyroidism (HypoT). However, it is not known whether they interfere in the cardiac response to coronary dysfunction. So, the aim of this work was to evaluate whether these plants interfere with the cardioprotection of HypoT after ischemia/reperfusion (I/R) in rats. In this model, HypoT was induced in rats by drinking methimazole for 15 days. Euthyroid (EuT) and HypoT rats drunk either Moff or Baf infusion during 7 days. Isolated perfused hearts were exposed to 20 min I/45min R inside a calorimeter, a model of stunning without infarct. Contractile pressure development (P, mmHg), diastolic pressure (LVEDP) and total heat rate (Ht, in mW/g) were measured. In EuT, Moff improved the postischemic contractile recovery (PICR) (105.0±16.4% of initial vs 69.4±6.0% in non-treated, p<0.05) and muscle economy (P/Ht). Baf slightly reduced PICR (40.4±6.7%) and significantly increased LVEDP. In HypoT hearts, Moff and Baf drastically reduced PICR (54.7±3.3% and 12.5±5.3% respectively vs 92.6±5.2% in non-treated, both p<0.05) as well as P/Ht, while increased LVEDP. Cyclosporine-A reversed the Moff dysfunction but not that of Baf, which was neither reduced by diazoxide. Results show that under HypoT Moff induced the opening of mPTP which reduce postischemic recovery, and Baf worsened the dysfunction although it was not related to mitochondrial calcium overload. Results suggest that the use of these plants in hypothyroid individuals with risk of cardiac ischemic episodes requires precaution.